Reliable wife a novel - Goolrick, Robert (Chapel Hill : Algonquin Books of Chapel Hill, 2010)
Ralph Truitt, a wealthy businessman with a troubled past who lives in a remote nineteenth-century Wisconsin town, has advertised for a reliable wife; and his ad is answered by Catherine Land, a woman who makes every effort to hide her own dark secrets.
Keywords: Marriage; Family secrets; Wisconsin -- History -- 19th century; Historical fiction; Domestic fiction